2020
DOI: 10.1016/j.csbj.2020.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania: Responding to environmental signals and challenges without regulated transcription

Abstract: Here we describe the non-canonical control of gene expression in Leishmania , a single-cell parasite that is responsible for one of the major neglected tropical diseases. We discuss the lack of regulated RNA synthesis, the post-transcriptional gene regulation including RNA stability and regulated translation. We also show that genetic adaptations such as mosaic aneuploidy, gene copy number variations and DNA sequence polymorphisms are important means for overcoming drug challenge and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 112 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…Indeed, aneuploidies have been widely reported in natural T. cruzi populations, and although CCNV varies among and within DTUs, it seems constant within a given population ( Schwabl et al, 2019 ; Reis-Cunha et al, 2015 ; Reis-Cunha et al, 2018 ). While in many multicellular organisms, aneuploidy is known to have severe consequences, in trypanosomatids it represents an important mechanism for rapidly overcoming environmental diversity ( Reis-Cunha et al, 2018 ; Prieto Barja et al, 2017 ; Bussotti et al, 2018 ; Grünebast and Clos, 2020 ). Aneuploidy is reversed quickly once the benefits of an extra chromosome expire, as observed in P2 aneuploidies in chromosomes 2 and 21.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aneuploidies have been widely reported in natural T. cruzi populations, and although CCNV varies among and within DTUs, it seems constant within a given population ( Schwabl et al, 2019 ; Reis-Cunha et al, 2015 ; Reis-Cunha et al, 2018 ). While in many multicellular organisms, aneuploidy is known to have severe consequences, in trypanosomatids it represents an important mechanism for rapidly overcoming environmental diversity ( Reis-Cunha et al, 2018 ; Prieto Barja et al, 2017 ; Bussotti et al, 2018 ; Grünebast and Clos, 2020 ). Aneuploidy is reversed quickly once the benefits of an extra chromosome expire, as observed in P2 aneuploidies in chromosomes 2 and 21.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aneuploidies have been widely reported in natural T. cruzi populations, and although CCNV varies among and within DTUs, it seems constant within a given population 13,31,36 . While in many multicellular organisms, aneuploidy is known to have severe consequences, in trypanosomatids it represents an important mechanism for rapidly overcoming environmental diversity [36][37][38][39] . Aneuploidy is reversed quickly once the benefits of an extra chromosome expire, as observed in P2 aneuploidies in chromosomes 2 and 21.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription termination occurs at the end of each polycistronic transcription unit and is determined by the presence of the base J ( van Luenen et al., 2012 ; Reynolds et al., 2016 ; Kieft et al., 2020 ). However, it is commonly stated in the literature that in the absence of transcriptional regulation, the regulation of protein expression in these parasites is mediated by post-transcriptional events, such as RNA degradation, translation control, and protein degradation ( Clayton and Shapira, 2007 ; Grünebast and Clos, 2020 ; Karamysheva et al., 2020 ). Several studies have shown that chromosomal copy number can be associated with transcription levels, supporting the notion that expression control occurs after transcription ( Dumetz et al., 2017 ; Iantorno et al., 2017 ; Patino et al., 2019 ).…”
Section: The Genome Of Leishmania Is Atypicalmentioning
confidence: 99%